Hemobilia in a child due to right hepatic artery pseudoaneurysm: Multidetector-row computed tomography demonstration - Nisar A Wani; Tariq A Gojwari; Naseer A Khan; Tasleem L Kosar (The Saudi Journal of Gastroenterology, 2011)
We present a case of a 12-year-old boy who developed upper gastrointestinal bleeding in the form of hematemesis and melena 1 month after blunt trauma to liver. Computed tomography (CT) angiography with multidetector-row CT demonstrated pseudoaneurysm of right hepatic artery related to old liver laceration to be the cause of the bleeding. Pseudoaneurysm was resected using the roadmap provided by CT angiography findings.